Epigenetic Switch–Induced Viral Mimicry Evasion in Chemotherapy-Resistant Breast Cancer - Deblois, Geneviève; Tonekaboni, Seyed Ali Madani; Grillo, Giacomo; Martinez, Constanza; Kao, Yunchi Ingrid; Tai, Felicia; Ettayebi, Ilias; Fortier, Anne-Marie; Savage, Paul; Fedor, Alexandra N.; Liu, Xiaojing; Guilhamon, Paul; et al. (Cancer discovery, 2020)
Tumor progression upon treatment arises from preexisting resistant cancer cells and/or adaptation of persister cancer cells committing to an expansion phase. Here, we show that evasion from viral mimicry response allows the growth of taxane-resistant triple-negative breast cancer (TNBC). This is enabled by an epigenetic state adapted to taxane-induced metabolic stress, where DNA hypomethylation over loci enriched in transposable elements (TE) is compensated by large chromatin domains of H3K27me3 to warrant TE repression. This epigenetic state creates a vulnerability to epigenetic therapy against EZH2, the H3K27me3 methyltransferase, which alleviates TE repression in taxane-resistant TNBC, leading to double-stranded RNA production and growth inhibition through viral mimicry response. Collectively, our results illustrate how epigenetic states over TEs promote cancer progression under treatment and can inform about vulnerabilities to epigenetic therapy. SIGNIFICANCE: Drug-resistant cancer cells represent a major barrier to remission for patients with cancer. Here we show that drug-induced metabolic perturbation and epigenetic states enable evasion from the viral mimicry response induced by chemotherapy in TNBC. These epigenetic states define a vulnerability to epigenetic therapy using EZH2 inhibitors in taxane-resistant TNBC.See related commentary by Janin and Esteller, p. 1258.This article is highlighted in the In This Issue feature, p. 1241.Tumor progression upon treatment arises from preexisting resistant cancer cells and/or adaptation of persister cancer cells committing to an expansion phase. Here, we show that evasion from viral mimicry response allows the growth of taxane-resistant triple-negative breast cancer (TNBC). This is enabled by an epigenetic state adapted to taxane-induced metabolic stress, where DNA hypomethylation over loci enriched in transposable elements (TE) is compensated by large chromatin domains of H3K27me3 to warrant TE repression. This epigenetic state creates a vulnerability to epigenetic therapy against EZH2, the H3K27me3 methyltransferase, which alleviates TE repression in taxane-resistant TNBC, leading to double-stranded RNA production and growth inhibition through viral mimicry response. Collectively, our results illustrate how epigenetic states over TEs promote cancer progression under treatment and can inform about vulnerabilities to epigenetic therapy. SIGNIFICANCE: Drug-resistant cancer cells represent a major barrier to remission for patients with cancer. Here we show that drug-induced metabolic perturbation and epigenetic states enable evasion from the viral mimicry response induced by chemotherapy in TNBC. These epigenetic states define a vulnerability to epigenetic therapy using EZH2 inhibitors in taxane-resistant TNBC.See related commentary by Janin and Esteller, p. 1258.This article is highlighted in the In This Issue feature, p. 1241.